1954
DOI: 10.2134/agronj1954.00021962004600100004x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Legumes as Influenced by the Rate of Sowing the Oat Companion Crop1

Abstract: LARGE proportion of the stands of small-seeded legumes A in the North Central Region of the United States is established with a conipanion crop of spring grain. This spring grain is principally oats. In Wisconsin, over 90% of the legume seedings are mad? in this manner. A companion crop such as oats competes with the legume seedlings in varying degrees for light and moisture, and for mineral nutrients if soil fertility has not been properly ndjusted. Limitations of light may become the dominant factor in compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
1

Year Published

1960
1960
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 5 publications
1
21
1
Order By: Relevance
“…Stahler (7) showed that the suppression of bindweed by crops was mainly due to shading. Smith et al (6) and Klebesadel and Smith (3) have shown that the shade cast by cereal crops results in a considerable reduction in the growth of pasture species.…”
Section: Introductionmentioning
confidence: 99%
“…Stahler (7) showed that the suppression of bindweed by crops was mainly due to shading. Smith et al (6) and Klebesadel and Smith (3) have shown that the shade cast by cereal crops results in a considerable reduction in the growth of pasture species.…”
Section: Introductionmentioning
confidence: 99%
“…SEEGMILLER The growth of a legume grown as a companion with a grass has been shown by many workers (3,4,5,8,10,11,15) to he less than when the legume is grown in pure stand.…”
mentioning
confidence: 99%
“…Explanations for this growth reduction of the legume include competition for light (5,6), soil moisture (11,15), nutrients (1,4,7,9,10,13), excretion of toxic materials (2,12,14), and effects of the microflora (12).…”
mentioning
confidence: 99%
“…After three years, the cover percentages were 13,6, and 4 for birdsfoot trefoil and 89, 59, and 77 for crown vetch, respective to the above grasses.…”
Section: Introductionmentioning
confidence: 99%
“…Although advice against using too much rye grass in a mixture has been offered (44,45), ryegrass has not been found a problem in other instances (15). Either rye grass or a small grain have been used as cover crops in other instances (3,30,39,40,47,59). …”
Section: Introductionmentioning
confidence: 99%